2016
DOI: 10.15252/emmm.201606566
|View full text |Cite
|
Sign up to set email alerts
|

Nec‐1 alleviates cognitive impairment with reduction of Aβ and tau abnormalities inAPP/PS1 mice

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive symptoms of learning and memory deficits. Such cognitive impairments are attributed to brain atrophy resulting from progressive neuronal and synaptic loss; therefore, alleviation of neural cell death is as an important target of treatment as other classical hallmarks of AD, such as aggregation of amyloid‐β (Aβ) and hyperphosphorylation of tau. Here, we found that an anti‐necroptotic molecule necrostatin‐1 (Nec‐1) directly targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 70 publications
(85 reference statements)
4
75
0
Order By: Relevance
“…In conclusion, we have demonstrated that RGC death signaling pathways are active in a regionspecific manner after blunt ocular injury, with necroptotic-dependent mechanisms likely driving a reduction in RGC numbers at the center of the impact site. The inhibition of necroptosis using pharmacological inhibitor, Nec-1s, preserved the number of RBPMS + and BRN3A + RGC compared to In line with our findings, RGC are also protected by the inhibition of necroptosis in other models of RGC death, including glaucoma [62] and retinal ischemia-reperfusion injury [63], and other models of neuronal disease and degeneration, including amyotrophic lateral sclerosis [64][65][66], Alzheimer's disease [26], Niemann-Pick disease [67], traumatic brain injury [28] and spinal cord injury [27]. The abundance of studies across multiple disease indicates the importance of necroptotic signaling in driving neuronal cell death.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, we have demonstrated that RGC death signaling pathways are active in a regionspecific manner after blunt ocular injury, with necroptotic-dependent mechanisms likely driving a reduction in RGC numbers at the center of the impact site. The inhibition of necroptosis using pharmacological inhibitor, Nec-1s, preserved the number of RBPMS + and BRN3A + RGC compared to In line with our findings, RGC are also protected by the inhibition of necroptosis in other models of RGC death, including glaucoma [62] and retinal ischemia-reperfusion injury [63], and other models of neuronal disease and degeneration, including amyotrophic lateral sclerosis [64][65][66], Alzheimer's disease [26], Niemann-Pick disease [67], traumatic brain injury [28] and spinal cord injury [27]. The abundance of studies across multiple disease indicates the importance of necroptotic signaling in driving neuronal cell death.…”
Section: Discussionsupporting
confidence: 88%
“…RIPK1 expression is elevated in a rat intracerebral hemorrhage model and its inhibition or genetic knockdown reduces brain injury severity [25]. Further, in a mouse model of Alzheimer's disease (APP/PS1 mice) treatment with necroptosis inhibitor Necrostatin-1 (Nec-1) reduces cognitive impairments, β-amyloid and tau abnormalities [26]. Nec-1 also improves histopathology and function in models of traumatic brain and spinal cord injury [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…47 Moreover, bimolecular binding between RIP kinase and A β was observed. 47 Interaction between these two proteins in the extracellular and luminal regions might be involved in A β -related cell death pathology in AD and therefore might serve as a potential drug target for the disease.…”
Section: Alzheimer's Diseasementioning
confidence: 98%
“…The stock solution was diluted 40 times with sterile PBS before use in order to obtain 2.5% DMSO and 0.625 μg/μl necrostatin-1. Subsequently, necrostatin-1 was administered by intraperitoneal injection (6.25 mg/kg) during the stress period, once every 3 days ( Yang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%